Splash - Howard, Ron, 1954-; Grazer, Brian, 1953-; Ganz, Lowell, 1948-; Mandel, Babaloo; Friedman, Bruce Jay, 1930-; Hanks, Tom.; Hannah, Daryl; Levy, Eugene, 1946-; Candy, John.; Goodman, Dody.; Greene, Shecky; Schull, RIchard B.; et al. (Burbank, CA : Buena Vista Home Entertainment, 2004)
The story of a workaholic who thinks he will never find love and the mermaid who comes ashore to find him and prove him wrong.
Originally produced as a motion picture in 1984.
Based on a story by Brian Grazer.
Special features include original Tom Hanks and Daryl Hannah auditions taped with director Ron Howard, "Making a splash": Babaloo Mandel, Brian Grazer, Daryl Hannah, Eugene Levy, John Candy, Lowell Ganz, Ron Howard and Tom Hanks reminisce on making the film, audio commentary: Director Ron Howard, producer Brian Grazer and writers Lowell Ganz & Babaloo Mandel share their thoughts on the film.
Music, Lee Holdridge ; editors, Daniel P. Hanley, Michael Hill ; director of photography, Don Peterman ; screen story by Bruce Jay Friedman.
Tom Hanks, Daryl Hannah, Eugene Levy, John Candy, Dody Goodman, Shecky Greene, Richard B. Schull, Bobby Di Cicco.
MPAA rating: PG.
Keywords: Mermaids -- Drama; Sirenas -- Teatro; Mermaids; Romantic comedy films; Comedy films; Fiction films; Feature films; Film adaptations; Video recordings for the hearing impaired; Comedy films; Drama; Feature films; Fiction films; Film adaptations; Romantic comedy films; Video recordings for the hearing impaired